FACTORS INFLUENCING CLOUD COMPUTING ADOPTION IN SMALL MEDIUM ENTERPRISES (Journal of Information and Communication Technology, 2017)
Cloud computing offers information technology (IT) infrastructure, platform, and various applications via the Internet with minimum start-up cost, network access to a shared pool of configurable computing resources, and pay-per-use services. Although the potential for cloud computing is evident and much of the extant research has been carried out on cloud computing adoption, empirical studies on the factors that influence cloud computing adoption in the Malaysian Small and Medium Enterprises (SMEs) are, however, lacking. The objective of this study was to examine the factors that influence cloud computing adoption by the SMEs. We conducted a quantitative survey-based study to examine the relationship between perceived benefits, top management support, IT resources, external pressure, and cloud computing adoption. A free-form comment provided at the end of each section of the survey questionnaire was treated as qualitative data. We find that IT resources and external pressure significantly influence cloud computing adoption. Nonetheless, there is not enough evidence to support perceived benefits and top management support as significant factors of cloud computing adoption.